2017
DOI: 10.1002/ccr3.863
|View full text |Cite
|
Sign up to set email alerts
|

Giant condyloma acuminatum–malignant transformation

Abstract: Key Clinical Message Giant condyloma acuminata are associated with malignant transformation in up to 50% of cases, high recurrence rate, and poor prognosis. Treatment strategies have included wide local excision, abdominopelvic resection, and addition of radiotherapy and adjuvant and/or neoadjuvant systemic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…GCA features tendency toward local recurrence and conversion into squamous cell carcinoma (Chao & Gibbs, ; Papapanagiotou et al, ). The risk of recurrence in the anorectal and perianal regions after excision is 60–66%, with an overall mortality of 20–30%.…”
Section: Discussionmentioning
confidence: 99%
“…GCA features tendency toward local recurrence and conversion into squamous cell carcinoma (Chao & Gibbs, ; Papapanagiotou et al, ). The risk of recurrence in the anorectal and perianal regions after excision is 60–66%, with an overall mortality of 20–30%.…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocyte subsets disorder can lead to imbalance of Th1/Th2 ratio, that is, the secretion of IL-2 and IFN-γ and other cytokines by Th1 cell decrease, while the secretion of IL-4 and IL-10 and other cells factors by Th2 cells increase. Reduced Th1/Th2 ratio is closely correlated with the development of CA ( 11 , 12 ). Erman-Vlahovic et al ( 13 ) found that peripheral blood levels of IL-2 and IFN-γ were significantly lower, while levels of IL-4 and IL-12 were significantly higher in CA patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…When SCC occurs in the context of GCA, management must be approached from the context of the patient and sometimes, only palliative measures can be offered to avoid more comorbidities [ 24 ].…”
Section: Clinical Presentationmentioning
confidence: 99%